IDENTIFIKASI BAKTERI AEROB GRAM NEGATIF DAN GRAM POSITIF MENGGUNAKAN METODE KONVENSIONAL DAN OTOMATIK - Patricia M. Tauran; Irda Handayani; Nurhayana Sennang (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Choosing the method of bacteria identification is crucial to obtain accurate and quick results. This study will analyze the identificationresults of Gram negative and Gram positive from aerobic bacteria by examination using conventional and automatic methods at Dr.Wahidin Sudirohusodo Hospital Laboratory. A total of 85 samples consisting of 66 Gram negative bacteria and 19 Gram positive bacteriawere identified using conventional and automated methods. In this study, there was some correspondent identification result betweenthe conventional as well as the automated methods, namely 31.5% for Gram negative bacteria and 30.8% for Gram positive bacteria.However, the non-correspondent identification result between conventional and automated methods was found greater, namely, 68.5%for Gram negative bacteria and 69.2% for Gram positive bacteria. The non-correspondent identification result was due to the developmentof bacterial taxonomy and the differences of numbers and types of the biochemical tests between conventional and automatic methods.Bacteria identification using automated method is more accurate and faster than the conventional method, so it is recommended usingthis particularly for the laboratory and educational referral center.